2009
DOI: 10.1128/jcm.01238-09
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Management of Invalid GeneXpert Enterovirus Results Obtained with Cerebrospinal Fluid Samples: a 2-Year Study

Abstract: A total of 525 cerebrospinal fluid (CSF) samples submitted during the 2007 and 2008 enteroviral seasons were included in a study to determine the prevalence of and potential risk factors for invalid Cepheid GeneXpert enterovirus assay (GXEA) results, as well as possible solutions for the problem. The invalid GXEA results were reported for 43 (8.2%) specimens and correlated with increased visibility of red blood cells (P < 0.0001) but not with CSF xanthochromia and clotting. Invalid GXEA result rates were marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The results used for comparative analysis with those obtained with the reference assay used in the core laboratory on the molecular virology diagnostics platform [5] were those recorded in the biological validation network system of the hospital. There are major points concerning these results: (i) the PPV of the POC-operated-Xpert EV kit was excellent (97.6%); (ii) the 16% 'indeterminate' results were of the same order of magnitude as results reported previously [8]; and (iii) these 16% indeterminate results were not included in the calculation of Sensibility, Specificity, PPV, and negative predictive value, because our goal was not to evaluate the intrinsic technical value of the Xpert EV kit, but rather to produce an estimate of its value in a real-life POC strategy for EV RNA detection. In these conditions, POC-'indeterminate' results (not validated) were not considered to be useful for clinicians, and were therefore not transmitted as results.…”
Section: Discussionsupporting
confidence: 61%
“…The results used for comparative analysis with those obtained with the reference assay used in the core laboratory on the molecular virology diagnostics platform [5] were those recorded in the biological validation network system of the hospital. There are major points concerning these results: (i) the PPV of the POC-operated-Xpert EV kit was excellent (97.6%); (ii) the 16% 'indeterminate' results were of the same order of magnitude as results reported previously [8]; and (iii) these 16% indeterminate results were not included in the calculation of Sensibility, Specificity, PPV, and negative predictive value, because our goal was not to evaluate the intrinsic technical value of the Xpert EV kit, but rather to produce an estimate of its value in a real-life POC strategy for EV RNA detection. In these conditions, POC-'indeterminate' results (not validated) were not considered to be useful for clinicians, and were therefore not transmitted as results.…”
Section: Discussionsupporting
confidence: 61%
“…(Goldenberg 2012) Sample adequacy control failures could have also been caused by potential interference of the TE buffer with the GeneXpert assay or potential inhibition of fecal/rectal material, which seemed to be resolved with the freeze-thaw cycle of the primary aliquot. Two prior studies also showed resolution of INVALID results in cerebral spinal fluid (CSF) samples on GeneXpert Assays by utilizing a free-thaw method (Seme 2008; Seters 2009). As seen in table 2 had only genital samples been analyzed and rectal sites not been screened 13 cases of CT infection and 6 cases of GC infection would have gone undiagnosed and subsequently untreated increasing transmission of these infections.…”
Section: Discussionmentioning
confidence: 99%
“…The actual rate of invalid results may be higher in routine practice. Sefers et al (17) reported an 8.2% invalid rate over a 2-year period of routine use. These authors found that either a 1:5 sample dilution of CSF in saline, or freezing and thawing the undiluted CSF markedly reduced the invalid rate with minimal impact on the sensitivity of the assay.…”
Section: Discussionmentioning
confidence: 99%